Screening For Pulmonary Hypertension With Multidetector Computed Tomography Among Patients With Severe Aortic Stenosis Undergoing Transcatheter Aortic Valve Implantation - O'Sullivan, Crochan J.; Montalbetti, Matteo; Zbinden, Rainer; Kurz, David J.; Bernheim, Alain M.; Liew, Aaron; Meyer, Matthias R.; Tüller, David; Eberli, Franz R. (Frontiers in Cardiovascular Medicine, 2018)
Aim: To assess the accuracy of multi-detector computed tomography (MDCT) derived pulmonary vessel measurements in predicting pulmonary hypertension (PH) among patients with severe symptomatic aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI). Background: PH is common among patients with severe AS undergoing TAVI and is associated with adverse outcomes. MDCT is the imaging modality of choice to assess anatomical dimensions among patients selected for TAVI. Methods: 139 patients with severe AS undergoing TAVI with both CT scans and right heart catheterizations (RHC) were included. CT diameters of the main pulmonary artery (MPA), right (RPA) and left (LPA) and ascending aorta (AA) were measured. The relationship between CT measurements and PA pressures assessing using RHC was tested with linear regression. Results: The CT derived ratio of the diameter of the MPA to the diameter of the AA (PA/AAratio) correlated best with mean PA pressure (R2 = 0.48) and PA systolic pressure (R2 = 0.50). Receiver operating characteristic curve analysis showed that the PA/AAratio is a moderate predictor of pulmonary hypertension (AUC 0.74, 95% CI 0.65-0.83, p<0.0001) and that the optimal cut off point is 0.80 (sensitivity 56%, specificity 88%, positive predictive value 95.5%, negative predictive value 30.6% for PH). Conclusions: Elderly patients with severe AS and PA/AAratio values ≥0.80 on MDCT are more likely to have PH but PH cannot be reliably excluded among such patients with lower PA/AAratio values.